1987
DOI: 10.1051/jphyscol:1987170
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Surface Properties of Ice Using Nuclear Magnetic Resonance

Abstract: Pulsed nuclear magnetic resonance studies were carried out on small ice particles with large surface to volume ratios to investigate the so-called quasi-liquid layer (Q.L.L.) on an ice surface. The temperature dependence of features of the NMR spectra and dynamical properties such as the correlation the for rotational motion and the self diffusion coefficient of the Q.L.L. were described. The frequency of the rotational molecular motion and the self diffusion coefficient were larger than those of bulk ice by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 0 publications
8
87
2
1
Order By: Relevance
“…It is noteworthy that molecular dynamics simulations that evaluated diffusivities for surface water molecules in the disordered interface of ice agree with available experimental data by Nasello et al (2007) to within the quoted precision for the entire temperature range: at a temperature of T m − 9 K a diffusivity of ≈ 8 × 10 −10 m 2 s −1 was obtained, and 59 K below melting this value drops to 1.8 × 10 −11 m 2 s −1 . The finding that the coefficient of self-diffusion on the ice surface is similar to that of supercooled liquid casts some doubts on the earlier results by Mizuno and Hanafusa (1987) using nuclear magnetic resonance work on ice to deduce diffusivities. The water molecule self-diffusion coefficient was established for the temperature range from 253 K to the melting point and amounts to 2.2 × 10 −13 m 2 s −1 at 263 K, i.e.…”
Section: Diffusion Of Water At the Ice Surfacementioning
confidence: 39%
See 2 more Smart Citations
“…It is noteworthy that molecular dynamics simulations that evaluated diffusivities for surface water molecules in the disordered interface of ice agree with available experimental data by Nasello et al (2007) to within the quoted precision for the entire temperature range: at a temperature of T m − 9 K a diffusivity of ≈ 8 × 10 −10 m 2 s −1 was obtained, and 59 K below melting this value drops to 1.8 × 10 −11 m 2 s −1 . The finding that the coefficient of self-diffusion on the ice surface is similar to that of supercooled liquid casts some doubts on the earlier results by Mizuno and Hanafusa (1987) using nuclear magnetic resonance work on ice to deduce diffusivities. The water molecule self-diffusion coefficient was established for the temperature range from 253 K to the melting point and amounts to 2.2 × 10 −13 m 2 s −1 at 263 K, i.e.…”
Section: Diffusion Of Water At the Ice Surfacementioning
confidence: 39%
“…Interestingly, the water mobility across grain boundaries is two orders of magnitude smaller than the mobility at the ice surface (Nasello et al, 2005) approaching the values of Mizuno and Hanafusa (1987) discussed above. Thus, it seems that the water molecules' mobility at the surface and in grain boundaries are quite different, while the latter are still enhanced by more than 3 orders of magnitude over the bulk values (Mullins, 1957;Nasello et al, 2005).…”
Section: Diffusion Of Water In Grain Boundariesmentioning
confidence: 83%
See 1 more Smart Citation
“…The molecular-dynamics simulation found the onset of surface melting of the ͑0001͒ face began with high molecular rotational and translational mobility, at about −40°C. The discrepancy with experimental results ͑Beaglehole and Nason, 1980; Ocampo and Klinger, 1983;Furukawa et al, 1987;Mizuno and Hanafusa, 1987͒, which found that onset is much closer to T m , is usually ascribed to limitations of the pointcharge model of the water molecule which is used. Nevertheless, this study affords a detailed view of the interlinked changes of molecular orientation and diffusion attendant on surface melting of ice.…”
Section: Computer Studies Of Ice Premeltingmentioning
confidence: 77%
“…A number of experimental techniques, such as atomic force microscopy (AFM) [32], nuclear magnetic resonance (NMR) [33,34], X-ray diffraction [35], and photoelectron spectroscopy [36], have been used to study the structural properties of the surface of ice [37]. These experiments provide evidence for the existence of structural disorder at the surface at temperatures below the bulk melting point.…”
Section: Introductionmentioning
confidence: 99%